Would you be willing to zap your child's brain? Public perspectives on parental responsibilities and the ethics of enhancing children with transcranial direct current stimulation. Issue 1 (2nd January 2018) - Wagner, Katy; Maslen, Hannah; Oakley, Justin; Savulescu, Julian
ABSTRACT: Background: Transcranial direct current stimulation (tDCS) is an experimental brain stimulation technology that may one day be used to enhance the cognitive capacities of children. Discussion about the ethical issues that this would raise has rarely moved beyond expert circles. However, the opinions of the wider public can lead to more democratic policy decisions and broaden academic discussion of this issue.Methods: We performed a quantitative survey of members of the U.S. public. A between-subjects design was employed, where conditions varied based on the trait respondents considered for enhancement.Results: There were 227 responses included for analysis. Our key finding was that the majority were unwilling to enhance their child with tDCS. Respondents were most reluctant to enhance traits considered fundamental to the self (such as motivation and empathy). However, many respondents may give in to implicit coercion to enhance their child in spite of an initial reluctance. A ban on tDCS was not supported if it were to be used safely for the enhancement of mood or mathematical ability. Opposition to such a ban may be related to the belief that tDCS use would not represent cheating or violate authenticity (as it relates to achievements rather than identity).Conclusions: The wider public appears to think that crossing the line from treatment to enhancement with tDCS would not be in a child's best interests. However, an important alternative interpretation of our results is that lay people may be willing to use enhancers that matched their preference for "natural" enhancers. A ban on the safe use of tDCS for enhancing nonfundamental traits would be unlikely to garner public support. Nonetheless, it could become important to regulate tDCS in order to prevent misuse on children, because individuals reluctant to enhance may be likely to give in to implicit coercion to enhance their child.